Mormonism and American politics - Balmer, Randall Herbert; Riess, Jana (Religion, culture, and public life, 2016)
Joseph Smith's presidential ambitions / Richard Lyman Bushman -- Unpopular sovereignty : Brigham Young and the U.S. government, 1847-1877 / John G. Turner -- Polygamy in the nation's capitol : Protestant women and the 1899 campaign against B.H. Roberts / Jana Riess -- Eternal progression : Mormonism and American progressivism / Matthew Bowman -- Ezra Taft Benson and the conservative turn of "those amazing Mormons" / Jan Shipps -- Testimony and theology : the Mormon struggle with America's civil religion / Russell Arben Fox -- Chosen land, chosen people : religious and american exceptionalism among the Mormons / Philip L. Barlow -- Like father, unlike son : the governors Romney, the Kennedy paradigm, and the Mormon question / Randall Balmer -- A politically peculiar people : how Mormons moved into and then out of the political mainstream / David E. Campbell, Christopher F. Karpowitz, and J. Quin Monson -- "Twice-told tale" : telling two histories of Mormon-black relations during the 2012 presidential election / Max Perry Mueller -- Mormon women talk politics / Claudia L. Bushman -- On the "underground" : what the Mormon "yes on 8" campaign reveals about the future of Mormons in American political life / Joanna Brooks -- Mitt, Mormonism, and the media : an unfamiliar faith takes the stage in the 2012 U.S. presidential election / Peggy Fletcher Stack